Quality of life in children and adolescents with congenital heart disease - Apóstolo, Jorge Manuel Amado (2016)
Purpose: The Quality of life is currently a major topic discussed in our society. The World Health Organization (WHO) has been developing a unifying and transcultural definition of QOL. They considered it as 'the individual's perception of his or her position in life, within the cultural context and value system he or she lives in, and in relation to his or her goals, expectations, parameters and social relations. It is a broad ranging concept affected in a complex way by the person's physical health, psychological state, level of independence, social relationships and their relationship to salient features of their environment (WHOQOL, 1997, p. 1). Congenital heart disease is the most prevalent congenital disease in Portugal. Despite the advances in cardiac treatment and an early correct diagnosis that could increase the survival of children with congenital heart disease, this condition influences the quality of life of children, adolescents and their parents. Knowing the perception of quality of life could help healthcare professionals, nurses in particular, providing suited care to the needs of these families, establishing priorities in their interventions, sensing predictors of a poor quality of life, promoting adherence to treatment and boosting compliance with treatment, and fostering greater satisfaction for these children, adolescents and their parents. 'As part of broader research and with the awareness that the chronic conditions could impact the quality of life and considering that all advances on treating congenital cardiac diseases we have defined this main objective: To determine the quality of life in children and adolescents with congenital heart disease (CHD) and the perception of their parents, as well as factors that influence it. Methods: It is a quantitative, descriptive and correlational research. The data collection tool was a questionnaire, which consisted of four parts: socio-demographic and educational characteristics, clinical characteristics, and quality of life, obtained using the Pediatric Cardiac Quality of Life Inventory ? PCQLI - (Marino, Tomlinson, Wernovsky, Drotar , Newburger, Mahony et al., 2010) translated into Portuguese. Data collection took place between February and July 2014, in compliance with ethical research guidelines. The sample comprised 59 children, 59 parents of children, 80 adolescents and 80 parents of adolescents. Results: The results indicated that children, adolescents, and their parents have high level of perceived health. The results are similar in all groups: children and parents and adolescents and parents. In the group of children, we observed the classification of "Good" in 66.10%, followed by the "Very Good" at 18.65% and "fair" in 15.25% of cases. The parents of the children responded in about half the cases that the health of their children was "good" (50.85%), "very good" in 30.51% "fair" in 11.86% and "Excellent "in 6.78%. In turn, the group of adolescents can be seen that 46.25% rate their health as "good", 32.50% as "very good", 16.25% as "Average" and 5% as "Excellent". Parents of teenagers classify the health of their children mostly as "good" in 42.50%, 31.25% as "very good", 20% as "fair" and 6.25% as "excellent". To point out that none of the respondents pointed out the option of a health status "Bad". About the quality of life, in general the results indicated that children, adolescents and their parents have high levels of quality of life, and that perceptions of parents and children are similar. Only in the children?s group (8 to 12 years old), was no influence of socio-demographic, school or clinical variables on quality of life observed. For adolescents (13 to 18 years old), school, special education, school retention, the age of diagnosis of congenital heart disease, cardiac catheterization and surgical intervention influenced their quality of life. Perception of quality of life of parents of children and of adolescents was influenced by socio-demographic and clinical variables. The results partly agree with the literature in this field. About the influence of some variables: The perception of quality of life expressed by children and adolescents with congenital heart disease and parents are related, with statistical significance. There were no statistically significant relationships between the quality of life of children and adolescents and their age, gender or socioeconomic status. Adolescents differ statistically significant between their quality of life and their education, the frequency of special education and the existence of grade retention. The severity of heart disease, the number of cardiac catheterizations or surgery and the presence of other health disorders are unrelated to the quality of life of children and adolescents. Adolescents revealed that the level of quality of life is influenced by the age of diagnosis of CHD by cardiac catheterization and surgery. For parents of children and adolescents gender and their education don?t influence their perception of quality of life. Only the socioeconomic status of parents of teens has statistically significant difference to quality of life. Parents of children and adolescents do not show statistically significant relationship between the perceived level of quality of life and severity of disease, age at diagnosis, the number of surgical interventions and the existence of other health disorders. There is a relationship of statistical significance between cardiac catheterization and the perceived quality of life by parents of adolescents; between the number of cardiac catheterizations and the perception of quality of life of parents of children; and between performing surgery and the perception of parents of children and adolescents. Conclusion: To analyze the quality of life of children and adolescents with CHD must be a key focus of attention in caring for this population, allowing the identification of individual differences, interests, preferences, and prevent potential problems. The knowledge acquired along with clinical experience contributes to improve the quality of life of children and families, facilitating their growth, psycho-emotional development and social integration. Nevertheless, the reading and interpretation of these results must be prudent and cautious, there are limitations to this research, including: the use of a range of specific quality of life for the Congenital heart disease in children, adolescents, and parents but whose validation process could not be completed in this study; the low prevalence of severe conditions in our sample; the absence of national studies to enable comparison with the results obtained. We intend to continue the process of validation of instrument and enlarge the research to Lisbon and Oporto, other major centers where the cardiac conditions can be treated.